Traditional Malay couched embroidery "tekat benang emas" and community in Padang Changkat Kuala Kangsar, Perak / Farah Hanna Ahmad Fuad, Wan Nur Rukiah Mohd Arshard, Murni Zainal .. [et al.] - Ahmad Fuad, Farah Hanna; Mohd Arshard, Wan Nur Rukiah; Zainal, Murni; Mohamed Noor, Nur Azdli (2022)
Sungai Perak is the second longest river system in Peninsular Malaysia and flows along 400km of the river basin that consists of traditional villages, architecture, and royal tombs that hold many mysteries in the long socio-cultural and economic history of the traditional Perak Malays. Kuala Kangsar's cultural inheritance from the past is significant because it is the evidence of human activity from traditional settlement through periods of colonialism to the present day in the built and natural environment (Mohd Sabrizaa & Sufian, 2009). Malay art, architecture, and civilization have often been the inherent manifestation of its culture and belief. For example, Ubudiah Mosque is one of the most recognized monuments in the district of Kuala Kangsar and "Seni Tekat" is one of the oldest crafts that has been practiced since the 10th century by the Malay community for their royal ornaments, as a luxurious and prestigious textile. A few researchers also have general references to the different types of art and crafts from Perak and have emerged as a topic of interest in the last few years. The art and crafts of this region represent one of the most significant achievements of the civilization, which is part of the legacy of Perak Malay craftsmanship (Kamaruddin Z. et al., 2013).